Flavour characterisation of fresh and processed pennywort (Centella asiatica L.) juices - Pronprapa Wongfhun (2018)
The flavour characteristics of fresh and processed pennywort juices treated by pasteurisation, sterilisation and high pressure processing (HPP) were investigated by using solid-phase micro-extraction combined with gas chromatography-mass spectrometry. Sesquiterpene hydrocarbons comprise the major class of volatile components present and the juices had a characteristic smell due to the presence of volatile compounds including β-caryophyllene, humulene, E-β-farnesene, α-copaene, alloaromadendrene and β-elemene. All processing operations caused a reduction in the total volatile concentration, but HPP caused more volatile acyclic alcohols, aldehydes and oxygenated monoterpenoids to be retained than pasteurisation and sterilisation. Ketones were not present in fresh pennywort juice, but 2-butanone and 3-nonen-2-one were generated in all processed juices, and 2-nonanone and 2-hexanone were present in pasteurised and sterilised juices. Other chemical changes including isomerisation were also reduced by HPP compared to pasteurisation and sterilisation. © 2009 Elsevier Ltd. All rights reserved.